High inhibition of Paenibacillus larvae and Listeria monocytogenes by Enterococcus isolated from different sources in Tunisia and identification of their bacteriocin genes. (1st July 2014) - Jaouani, I.; Abbassi, M.S.; Alessandria, V.; Bouraoui, J.; Ben Salem, R.; Kilani, H.; Mansouri, R.; Messadi, L.; Cocolin, L.
Abstract: A total of 300 isolates of Enterococcus, from different sources including faeces of poultry, cow and sheep, raw milk, ricotta cheese and water, in Tunisia, were screened for their antibacterial activity. Amongst them, 59 bacteriocin‐producing strains were detected and identified by molecular methods. Genes encoding for ent A, ent P, ent B, ent L50A/B, AS‐48 and bac 31 bacteriocins were targeted by PCR. The bacteriocin‐producing strains were assigned to the species Enterococcus faecium, Enterococcus faecalis, Enterococcus hirae, Enterococcus mundtii and Enterococcus durans, respectively, 34, 19, 3, 2 and 1 isolates. Antimicrobial activity was specifically observed against different spoilage and pathogenic micro‐organisms, such as Listeria monocytogenes, Listeria innocua, Listeria ivanovii, Escherichia coli, Ent. faecalis, Staphylococcus aureus, Salmonella enterica serovar Enteritidis and Paenibacillus larvae . The inhibitory activity was totally lost after proteinase K treatment, thereby revealing the proteinaceous nature of the antimicrobial compound. Only three bacteriocin genes, namely entP, entA and ent L50A/B were detected in the isolates included in this study. Enterocins A and P were the most frequent genes and they were found in 55 (93·2%) and 39 isolates (66·1%), respectively, followed by enterocin L50A/B present in 27 isolates (45·7%). These newly identified bacteriocin‐producing enterococci have the potential to be used in bio‐preservation of food as well as biological control of foulbrood disease. Significance and Impact of the Study: Enterococci possess interesting properties not only for the food industry, but also for animal and human health. The antimicrobial potential of these bacteria includes principally bacteriocin‐like molecules. With the aim of identifying bacteriocinogenic strains, a collection of 300 enterococci isolated from different origins were screened and their spectrum of action, as well as the gene encoding the bacteriocin, was determined. Fifty‐nine bacteriocin‐producing Enterococcus showed high activity against Listeria monocytogenes and Paenibacillus larvae, the causative agent of American foulbrood. Enterocins A, P and L50A/B were found in various combinations. The most important finding of this study is the growth inhibition of P. larvae due to bacteriocin‐producing Enterococcus, which opens up the possibility to use these strains to control the disease in honeybees.